A fast and robust iterative genome-editing method based on a Rock-Paper-Scissors strategy. Issue 2 (3rd December 2020) - Wang, Jichao; Sui, Xinyue; Ding, Yamei; Fu, Yingxin; Feng, Xinjun; Liu, Min; Zhang, Youming; Xian, Mo; Zhao, Guang
Abstract: The production of optimized strains of a specific phenotype requires the construction and testing of a large number of genome modifications and combinations thereof. Most bacterial iterative genome-editing methods include essential steps to eliminate selection markers, or to cure plasmids. Additionally, the presence of escapers leads to time-consuming separate single clone picking and subsequent cultivation steps. Herein, we report a genome-editing method based on a Rock-Paper-Scissors (RPS) strategy. Each of three constructed sgRNA plasmids can cure, or be cured by, the other two plasmids in the system; plasmids from a previous round of editing can be cured while the current round of editing takes place. Due to the enhanced curing efficiency and embedded double check mechanism, separate steps for plasmid curing or confirmation are not necessary, and only two times of cultivation are needed per genome-editing round. This method was successfully demonstrated in Escherichia coli and Klebsiella pneumoniae with both gene deletions and replacements. To the best of our knowledge, this is the fastest and most robust iterative genome-editing method, with the least times of cultivation decreasing the possibilities of spontaneous genome mutations.